O ensino de história local : conhecendo o patrimônio de Muribeca/SE - Souza, Jorge Douglas Vieira Cabral (2022)
This work presents reflections arising from a research for a Professional Master's Degree in History Teaching (PROFHISTÓRIA) at the Federal University of Sergipe (UFS). This research seeks to analyze the relevance that exists between the teaching of local history and the material heritage of the city of Muribeca/SE from the observation, registration and research of changes and permanencies in the urban space. We are interested in reflecting on how the changes that have occurred in the material heritage and its surroundings help in the teaching of History and in the various possible approaches based on collective and shared memory in the experience of students in the community. In an attempt to answer this and other questions, we propose to develop a Didactic Project based on this theme, which received the following title: “Getting to know my city through photographs and visits to the Material Heritage”. In this sense, we try to develop the relationship between History and the enhancement of local identity through the material heritage of the city of Muribeca/SE. Our Didactic Project was developed to be carried out with students in the sixth year of elementary school at the Almirante Barroso State School in the City of Muribeca/SE. At first, the concept of heritage and field work with the collection of old photographs of the city will be addressed. In the second moment, the visit to the buildings shown in the photos is foreseen, allowing the students to work with permanence and changes. In a third moment, there will be the production of materials that will result in the fourth and final stage, the culmination of the project, with an exhibition of photos and texts produced by the students. As a result of this work, we hope to remedy the lack of teaching material on local history, especially the city of Muribeca/SE, and sharpen the feeling of belonging to heritage, contributing to its preservation.